The Mentor - Holsinger, Alexander M. (Victims & offenders, 2021)
Edward J. Latessa has been driving the evolution of correctional practice for several decades. Academics, practitioners, and policymakers throughout the United States and abroad seek Ed’s counsel as a result of his immense and ongoing research agenda, the development of practical tools and curricula, the establishment and growth of the University of Cincinnati’s academic programs and research centers, and his countless and accessible talks and presentations. A less visible but nonetheless important part of the aforementioned accomplishments is his mentoring of academics and practitioners. Ultimately, it is any scholar’s students who will continue the work of the mentor, and expand their impact on an evolving field. This essay attempts to offer an “inside look” of sorts using my own experiences working under Ed’s direction, while also noting other ways Ed has offered education and direction to myself and many others. Many fields, including perhaps especially the academy, rely on the transfer of knowledge from mentor to mentee, and Ed is a highly effective, colorful, and endlessly entertaining mentor. As a result of his tireless efforts, the practice of corrections benefits in innumerable ways, with policy, practice, and programming becoming more humane, just, and effective at evoking long-term behavioral change.